Written to be heard : recovering the messages of the Gospels - Borgman, Paul, 1940-; Clark, Kelly James, 1956-; Wolterstorff, Nicholas (Grand Rapids, MI. William B Eerdmans Publishing Company., 2019)
The words of the gospels were meant to be heard. While we can still appreciate the construction and grasp some understanding when we read, we miss much of the message because we're working in the wrong medium. In Written to Be Heard Paul Borgman and Kelly James Clark offer the keys to recovering the radical, relevant messages of each gospel as they were first heard. The shaping of the gospels for oral performances, which would have been obvious to ancient (mostly preliterate) listeners, is lost on even the best contemporary reader. With careful analysis of the gospel writers' particular voices within their own ancient literary context, Borgman and Clark equip readers to read as if hearing, focusing on overlapping patterns of hearing cues that shape each text and embed theological perspective
Foreword / by Nicholas Wolterstorff -- Preface -- Introduction -- Part one: The Gospel of Mark -- Part two: The Gospel of Matthew -- Part three: Luke-acts, I: the Gospel of Luke -- Part four: Luke-acts, II: the acts of the apostles -- Part five: The Gospel of John
Foreword statement from cover
Includes bibliographical references and indexes
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc